Moringa oleifera extract (Lam) attenuates Aluminium phosphide-induced acute cardiac toxicity in rats - Ahmed S. Gouda; Nagla A. El-Nabarawy; Samah F. Ibrahim (Toxicology Reports, 2018)
Background: Moringa oleifera extract (Lam) has many antioxidant and protective properties. Objective: to investigate the antioxidant activities of Lam in counteracting the high oxidative stress caused by acute sub-lethal aluminium phosphide (AlP) intoxication in rat heart. These activities will be detected by histopathological examination and some oxidative stress biomarkers. Methods: a single sub-lethal dose of Alp (2 mg/kg body weight) was administered orally, and Lam was given orally at a dose (100 mg/kg body weight) one hour after receiving AlP to rats. Results: aluminium phosphide caused significant cardiac histopathological changes with a significant increase in malondialdehyde (MDA); lipid peroxidation marker; and a significant depletion of antioxidant enzymes (catalase and glutathione reductase). However, treatment with Lam protected efficiently the cardiac tissue of intoxicated rats by increasing antioxidants levels with slight decreasing in MDA production compared to untreated group. Conclusions: This study suggested that Moringa oleifera extract could possibly restore the altered cardiac histopathology and some antioxidant power in AlP intoxicated rats, and it could even be used as adjuvant therapy against AlP-induced cardiotoxicity. Keywords: Toxicity, Aluminium phosphide, Cardiac toxicity, Oxidative stress, Moringa oleifera extract